Analisis Pola Hubungan Jenis dan Komponen Limbah Rumah Sakit Berdasarkan Tahun Pengamatan Menggunakan Model Log-Linear Tiga Dimensi - Maria Helena K. Goma; Maria A. Kleden; Robertus D. Guntur (Mathematics Department, Faculty of Sciences and Technology Unisda Lamongan, 2026)
Hospital waste has the potential to adversely affect human health and the environment if not properly managed. This study aims to analyze the relationship between waste type, waste components, and year of observation, and to determine the best three-dimensional log-linear model for waste data from Dr. Hendrikus Fernandes Larantuka Regional General Hospital for the period 2023–2025. The data used were secondary data from the Environmental Health Administration Department of Dr. Hendrikus Fernandes Larantuka Regional General Hospital. The variables analyzed included the year of observation, waste type, and waste components. The analysis was conducted using a three-dimensional log-linear model through a goodness-of-fit test, a partial association test, selection of the best model using the backward elimination method, and relative risk analysis. The results showed that the model fit the data based on the goodness-of-fit test, with a Pearson Chi-Square value of 2.170 and a significance level of 0.950 (>0.05). The partial association test indicated no significant association between waste type and waste components after controlling for year (p = 0.862). The best model obtained was the main effects model of waste components, with a Likelihood Ratio Chi-Square value of 2.943 and a significance level of 0.983 (>0.05). The relative risk analysis yielded an RR value of 2.32, indicating that the likelihood of solid waste components being present in non-infectious waste is 2.32 times greater than in infectious waste.